Customers' perceived e-service quality and its effect on customer satisfaction in airline service : acase study of Airasia - Chong Wei Yeong, author; Kamaruzzaman Abdul Rahim, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2012)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2012